Changing look AGN Mrk 590: broad-line region and black hole mass from photometric reverberation mapping. Issue 4 (8th October 2021) - Mandal, Amit Kumar; Schramm, Malte; Rakshit, Suvendu; Stalin, C S; Vijarnwannaluk, Bovornpratch; Rujopakarn, Wiphu; Poshyachinda, Saran; Kouprianov, Vladimir V; Haislip, Joshua B; Reichart, Daniel E; Sagar, Ram; Mathew, Blesson
ABSTRACT: We present the results of photometric reverberation mapping observations on the changing look active galactic nucleus Mrk 590 at z = 0.026. The observations were carried out from 2018 July to December using broad-band B -, R -, and narrow-band H α and S ii filters. The B band traces the continuum emission from the accretion disc, the R band encompasses both the continuum emission from the accretion disc and the redshifted H α line from the broad-line region (BLR), the S ii band contains the redshifted H α emission and the H α band traces the continuum emission underneath the S ii band. All the light curves showed strong variation with a fractional root-mean-square variation of 0.132 ± 0.001 in the B band and 0.321 ± 0.001 in H α line. From cross-correlation function analysis, we obtained a delayed response of H α line emission to the optical B -band continuum emission of $21.44^{+1.49}_{-2.11}$ d in the rest frame of the source, corresponding to a linear size of the BLR of 0.018 pc. This is consistent with previous estimates using H β . By combining the BLR size with the H α line full width at half-maximum of 6478 ± 240 km s −1 measured from a single-epoch spectrum obtained with the Subaru telescope, we derived a black hole mass of $1.96^{+0.15}_{-0.21}× 10^8 {\rm M}_{\odot }$ .